Perceived racial discrimination, heavy episodic drinking, and alcohol abstinence among African American and White college students. Issue 2 (3rd April 2017) - Wade, Jeannette; Peralta, Robert L.
ABSTRACT: Previous research has demonstrated that White college students are more likely to drink alcohol at a greater frequency and quantity compared to their African American counterparts. Examining race-related factors that structure alcohol use among college students remains an important area of research. In this study, we specifically examine perceived discrimination and its association with both heavy episodic drinking (HED) and alcohol abstinence among college students. Items that measured perceived racial discrimination in alcohol use contexts and demographic characteristics were used as independent and control variables. African American students were more likely to abstain from alcohol and less likely to engage in HED compared to their White counterparts. Results also suggest that students who believe their drinking will solicit race-based police bias have lower odds of engaging in HED and greater odds of alcohol abstention. We conclude that unsolicited policing, experienced by African Americans generally, and White Americans on campuses, explains effect sizes.